Evaluation of Pediatric Patients with Biliary Tract Dysfunction using Ultrasound Techniques - Burri, Rithwik Goud (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Despite advancements in surgical methods and post-transplant care, liver and kidney transplants still pose significant risks of complications such as graft rejection, infection, and severe consequences. These complications may emerge shortly after surgery or several months to years later. Early detection of complications in transplant recipients is crucial. Ultrasound (US) is the key technique for visually assessing transplanted organs and delivering diagnostic information on blood vessel opening and blood flow to organs. This study aimed to explore the potential of US techniques for evaluating pediatric patients with biliary tract dysfunction. Materials and Methods: The study included 128 children aged 7–14 years, with 100 children in the experimental group and 28 in the control group. The experimental group was divided into two subgroups: Group 1 consisted of 57 children with hypokinetic biliary dyskinesia and Group 2 consisted of 43 children with hypermotor dyskinesia of the biliary tract. Results: In cases of hypokinetic biliary dyskinesia, the motor function indicator significantly decreased below that of the control group (P < 0.01) and was twice as low as that of the hypermotor type (P < 0.001). In contrast, in group 2, this value exceeded that of the control group (P < 0.01). The study demonstrated that dynamic US indicators for functional disorders of the gallbladder (GB) have relatively high sensitivity (91%) and specificity (87%). Conclusion: This study identified variations in biliary tract function during US examinations in children with different forms of dyskinesia. Alterations in GB function affect the overall performance of the hepatobiliary system in pediatric patients.